Consumer Preferences on the Complementation of Mocaf Flour in Egg Peanut as a Leading Product of Dryland Plants - Setiawan, Teguh; Suroso, Erdi; Fadhallah, Esa Ghanim; Indraningtyas, Lathifa; Aritina, Rika (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
Indonesia is one of the largest wheat importing countries. This has led to the emergence of the nature of the dependence of the Indonesian people on wheat. Cassava is the largest carbohydrate source commodity in Indonesia compared to other carbohydrate sources. Cassava can be processed into several sources of raw materials, one of which has great potential is MOCAF. Modified Cassava Flour (MOCAF) is a modified cassava flour. In this project, the use of modified cassava flour with physical methods in the manufacture of egg nuts aims to determine the comparison of the complementation of physical method modified cassava flour with wheat flour to produce egg nuts with the best characteristics. The tools used are stove, oven, wok, basin and winnowing. While the ingredients used are cassava flour modified by physical method, wheat flour, tapioca, eggs, peanuts, sugar, salt, shallots, garlic, and vanilla. In the preliminary experiment, the control egg bean was made, then the main experiment was the manufacture of egg nut with 5 treatments and 3 replications. The treatment given was by using modified cassava flour with a formulation of 50%, 60%, 70%, 80%, and 90%. The form of observations made on the egg bean products that were tested included organoleptic tests. Based on the organoleptic test carried out, it was found that the egg bean which had the overall acceptance of the panelists towards the egg bean, the most preferred product was the egg bean with the use of 70% modified cassava flour.